ANALISIS KOMPETENSI GURU MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS NEGERI MEDAN DALAM PROGRAM MAGANG KEPENDIDIKAN MBKM - Revika Ananda Putri; Trisnawati Hutagalung; Lili Sartika; Febrina Azura; Syifa Indria; Chici Alwafiq (BAHAS, 2021)
Abstract   Education in the 2021 century requires students to be able to think critically and teachers or prospective educators must be able to master technology in presenting learning content and materials. Thus, the MBKM educational internship project conducted by Indonesian Language and Literature Education students offers Technological Pedagogical Content Knowledge (TPACK) and Higher Order Thinking Skills (HOTS) learning ambassadors to answer today's educational challenges. Teacher competence is an agent of learning in education. The application of the learning ambassador must be followed by the quality of personality competence, social competence, professional competence and good pedagogic competence of prospective educators. This type of research is descriptive with a quantitative approach. The research subjects were the MBKM program interns. The results of the analysis show that the competence of teachers in educational internship students is in good category with an average rating range of 7.16-8.09. The implementation of the internship is accompanied by evaluations from the civil expert validator, servant teachers and accompanying lecturers. Thus, internship students can improve and develop the quality of their competencies based on constructive criticism and suggestions.Keywords: TPACK, HOTS, Internship, and Competence